A Short economic history of modern Japan (Macmillan Press, 1981)
This book contains the fruits of a study of Japan's economic affairs which began during my time as a lecturer at the Nagoya Koto Shogyo Gakko between 1922 and 1925. The main emphasis was on industrial and financial development and on economic policy, although the study was not confined to those subjects.